PENGARUH TEKNOLOGI TERHADAP PRODUK DOMESTIK REGIONAL BRUTO (PDRB) PROVINSI DKI JAKARTA - Riduan Lubis; Johanna Maria Kodoatie (Universitas Diponegoro, 2013)
This study aims to examine the influence of technology to gross regional domestic product(GRDP) of DKI Jakarta in the year 1984 to 2010. Technology is one of the factors contributing tothe increasing output. In this study, technology is measured by capital per effective labor. Besidestechnology, output is also influenced by capital and labor.This study is using time series data. The analysis of time series data is done withregression analysis. The technic of variable estimation is named Ordinary Least Square (OLS),prepare using the software of Eviews 6.0The results showed that in Province DKI Jakarta, variable of technology and grossregional domestic product (GRDP) of DKI Jakarta have a positive and significant relationshipwhereby if the technology rises by Rp 1 then the gross regional domestic product of DKI Jakartawill increase by Rp 0,14. It shows that each year additional technology required to increase grossregional domestic product of DKI Jakarta.